Pengaruh Penerapan Prinsip Syariah terhadap Loyalitas Pelanggan di Hotel Dalwa Syariah Pasuruan - Miftakhul Arif Saifuddin Islami; Abdillah Mundir; Alimatul Farida (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This article discusses the importance of implementing sharia principles in the hotel industry, especially in the context of sharia dalwa hotels, with a focus on aspects of customer loyalty. Sharia principles provide a framework that is in accordance with Islamic values, such as justice, transparency and shared prosperity. This research identifies whether there is an influence between customer loyalty at Dalwa Syariah hotels on sharia principles and trust. Through analysis of primary and secondary data, the findings show that consistent application of sharia principles increases customer trust and satisfaction, which in turn strengthens their loyalty.